Grimm. Season two [videorecording (DVD)] - Giuntoli, David, 1980-; Hornsby, Russell; Mitchell, Silas Weir; Tulloch, Bitsie, 1981-; Roiz, Sasha, 1973-; Lee, R. T. (Reggie T.); Turner, Bree, 1977- (Grimm (Television program)., 2013)
Now fully embracing his identity as a Grimm, Portland homicide detective Nick Burkhardt tackles even more gruesome and bizarre crimes linked to creatures of lore. With the help of his partner Hank and Wesen confidants Monroe and Rosalee, Nick must face an ancient royal bloodline linked to the mysterious Captain Renard, all while fighting to keep from losing the love of his life forever.